Regulation of hippocampus-dependent memory by the zinc finger protein Zbtb20 in mature CA1 neurons - Ren, Anjing (Blackwell Science Inc, 2012)
The mammalian hippocampus harbours neural circuitry that is crucial for associative learning and memory. The mechanisms that underlie the development and regulation of this complex circuitry are not fully understood. Our previous study established an essential role for the zinc finger protein Zbtb20 in the specification of CA1 field identity in the developing hippocampus. Here, we show that conditionally deleting Zbtb20 specifically in mature CA1 pyramidal neurons impaired hippocampus-dependent memory formation, without affecting hippocampal architecture or the survival, identity and basal excitatory synaptic activity of CA1 pyramidal neurons. We demonstrate that mature CA1-specific Zbtb20 knockout mice exhibited reductions in long-term potentiation (LTP) and NMDA receptor (NMDAR)-mediated excitatory post-synaptic currents. Furthermore, we show that activity-induced phosphorylation of ERK and CREB is impaired in the hippocampal CA1 of Zbtb20 mutant mice. Collectively, these results indicate that Zbtb20 in mature CA1 plays an important role in LTP and memory by regulating NMDAR activity, and activation of ERK and CREB.